ANALYSIS OF INTERNATIONAL EXPERIMENTS ON THE DEVELOPMENT OF A SERVICE DOG IN LAW ENFORCEMENT AGENCIES IN A SPECIAL DIRECTION (ON THE EXAMPLE OF THE SERVICE DOG TRAINING METHODOLOGY OF THE CANINE SERVICE OF THE REPUBLIC OF LATVIA) - Karimjanova Munavvar Ibrakhimovna. (Scholar Express Journals, 2023)
This article covers the importance of the cynological service in the system of law enforcement bodies of the Republic of Uzbekistan, including the role and service activities of the National cynological Center in the system of customs authorities, the organization of certain shortcomings in the methodology of training service dogs for a general training course on the basis of Advanced International Also, scientific proposals and recommendations are presented on the creation of new training methods on the basis of Advanced International experience in the development and improvement of the educational and educational process in the training of service dogs in ensuring the economic security of our country.
Keywords: customs activities; dog training service; dog training; service dogs